Isolation and Screening of Lactic Acid Bacteria From Sumbawa Buffalo Milk (Bubalus bubalis) as Potential Starter Cultures - Harmoko, Deni; Ardyati, Tri; Jatmiko, Yoga Dwi (Graduate School, Universitas Brawijaya, 2022)
The Sumbawa buffalo (Bubalus bubalis) is one of the ruminant livestock in Indonesia that not only contributes to fulfilling meat requirements but also milk. Besides containing nutrients that are very beneficial for human health, buffalo milk is also a potential source of lactic acid bacteria (LAB) with technological and functional properties. Lactic acid bacteria have been utilized as starter cultures in various fermented products. This study aimed to isolate LAB from Sumbawa buffalo milk and to identify the potential isolate as a starter culture. The screening of LAB as a starter culture was based on some technological properties, including proteolytic activity, lipolytic activity, exopolysaccharide (EPS) production, antibacterial activity, antibiotic sensitivity, hemolytic activity, and acidification activity Data were analyzed statistically using one-way ANOVA and Tukey’s post hoc test at a 5% significance level. A total of 21 isolates were isolated from fresh buffalo milk, with a LAB total was 4.7x105 CFU.mL-1. All the isolates were characterized as Gram-positive with cocci-shaped. The SA8 isolate was selected as the most potential candidate as a starter culture because it has fulfilled the criteria such as the highest proteolytic activity, the lowest lipolytic activity, producing EPS, potential antagonistic activity against Bacillus cereus, Escherichia coli, and Salmonella Typhi, and sensitivity to cefazolin, intermediate to erythromycin and cinoxacin, non-pathogen, as well as the most rapid acidification activity. The SA8 isolate was identified as Enterococcus lactis with a similarity level of 99.99% towards strain BT159. This indigenous LAB was a potential starter culture of Sumbawa fermented buffalo milk to increase the diversification of products derived from buffalo milk. Keywords: Enterococcus lactis, lactic acid bacteria, technological properties, starter culture, Sumbawa buffalo milk.